2004
DOI: 10.1002/hep.20016
|View full text |Cite
|
Sign up to set email alerts
|

Viral features of lamivudine resistant hepatitis B genotypes A and D

Abstract: Viral differences among lamivudine resistant hepatitis B (HBV) genotypes have not been yet investigated. Therefore, we analyzed the characteristics of these viral strains in vivo. Fortyone patients carrying lamivudine resistant HBV were enrolled. Twenty-six patients (63%) carried resistant HBV genotype A (group A) and 15 patients (37%) carried resistant HBV genotype D (group D). The rate of reverse transcriptase 204I mutants was significantly higher in group D (67%) compared with group A (19%), whereas rt204V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 37 publications
(43 reference statements)
5
88
1
Order By: Relevance
“…12,13 However, in patients with a chronic HBV infection, an antiviral response as an indicator of future treatment outcomes has not yet been fully determined. Previous studies suggested that the HBV genotype, 14 the ALT level, 9,15 the degree of the decline of the HBV DNA level during therapy. 16,17 the presence of HBeAg, 15,18 the presence of core promoter mutations, 19 and HBV core-related antigens 20 were factors that could predict the emergence of YMDD mutants.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 However, in patients with a chronic HBV infection, an antiviral response as an indicator of future treatment outcomes has not yet been fully determined. Previous studies suggested that the HBV genotype, 14 the ALT level, 9,15 the degree of the decline of the HBV DNA level during therapy. 16,17 the presence of HBeAg, 15,18 the presence of core promoter mutations, 19 and HBV core-related antigens 20 were factors that could predict the emergence of YMDD mutants.…”
Section: Discussionmentioning
confidence: 98%
“…Using complex analysis, previous studies identified several factors predictive of emergence of YMDD mutants such as HBV genotype, 28 ALT level, 29,30 HBV DNA level before therapy, 28,[30][31][32] degree of decline of HBV DNA level during therapy, 33,34 presence of hepatitis B e antigen, 17,29,31,32,35 presence of core promoter mutations, 36 deletion of pre-S region, 37 and HBV core-related antigen. 38 We also showed that a slow decrease in HBV nucleic acid measured by the TMA-HPA is a marker of early emergence of mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Buti et al suggested that the emergence of lamivudine resistance were also comparable between genotypes A and D [122]. Nevertheless, studies from Germany and China indicated that there exist different YMDD mutational patterns among different lamivudine-resistant HBV genotypes [124,125]. For example, the frequency of rtM204I mutants is higher in genotypes C and D, whereas that of rtM204V is higher in genotypes B and A.…”
Section: Genotypesmentioning
confidence: 99%